Passive acoustic monitoring data recorded by recorder SV0002 at mooring AWI227-11 in the Weddell Sea, Southern Ocean, in 2010/2011 - Karolin Thomisch; Stefanie Spiesecke; Katharina Lefering; Sebastian Menze; Loretta Preis; Ilse Van Opzeeland; Olaf Boebel (PANGAEA, 2025)
Passive acoustic monitoring (PAM) data were collected by recorder SV0002 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 59.0503° S, 0.1105° E, mooring AWI227-11, in Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from December 2010 to December 2012, passive acoustic data were collected from December 2010 to August 2011 (recording period) by SV0002 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 1007 m depth and scheduled to record continuously at a sample rate of 5,333 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see the associated data processing report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).